2021
DOI: 10.1021/acs.jpcb.1c03193
|View full text |Cite
|
Sign up to set email alerts
|

Silinanyl Rhodamines and Silinanyl Fluoresceins for Super-Resolution Microscopy

Abstract: Single-molecule localization microscopy (SMLM) enables the visualization of biomolecules at unprecedented resolution and requires control of the fluorescent blinking (ON/OFF) states of fluorophores to detect single-molecule fluorescence without overlapping of the signals. Although SMLM probes based on the intramolecular spirocyclization of Si-xanthene fluorophores have been developed, fluorophores with lower ON/OFF ratios are required for SMLM visualization of high-density structures. Here, we describe a silin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For SMLM imaging, xanthene-based ''photo click'' chemistry has been widely explored. 194 In 2020, Morozumi et al developed a fluorogenic probe by incorporating a benzylchloropyrimidine unit, which is a known substrate for SNAP-tag, in the fluorogenic probe CP550. 195 The CP550-labeled BnClPy (a substrate for SNAP-tag) could be used to image live cells expressing SNAP-tag proteins in mitochondria.…”
Section: Small-molecule Fluorogenic Probes For Smlm Imagingmentioning
confidence: 99%
“…For SMLM imaging, xanthene-based ''photo click'' chemistry has been widely explored. 194 In 2020, Morozumi et al developed a fluorogenic probe by incorporating a benzylchloropyrimidine unit, which is a known substrate for SNAP-tag, in the fluorogenic probe CP550. 195 The CP550-labeled BnClPy (a substrate for SNAP-tag) could be used to image live cells expressing SNAP-tag proteins in mitochondria.…”
Section: Small-molecule Fluorogenic Probes For Smlm Imagingmentioning
confidence: 99%
“… [97] This means spontaneous blinking is possible, even when the intramolecular nucleophile remains a carboxy group. [98] Silicon‐rhodamine (SiR‐carboxyl, Figure 11 b) was used in super‐resolution imaging (STORM/GSDIM). [99] Iwanaga and co‐workers reported that changing the functionalization on the Si atom from dimethyl to a cyclic silanyl further increases the electrophilicity of the xanthene core.…”
Section: Photochemical Mechanisms Of Fluorophores Used In Smlmmentioning
confidence: 99%
“… [99] Iwanaga and co‐workers reported that changing the functionalization on the Si atom from dimethyl to a cyclic silanyl further increases the electrophilicity of the xanthene core. [98] This increases the likelihood of spirocyclization and results in a lower on/off ratio. They also further modified the rhodamine scaffold by changing the amino auxochrome groups to give a 7‐azabicyclo[2.2.1]heptane substituted analogue, SiliR14 (Figure 11 b), which showed superior photostability and spontaneous blinking properties.…”
Section: Photochemical Mechanisms Of Fluorophores Used In Smlmmentioning
confidence: 99%
“…Silicon‐bridged rhodamine analogues have lower p K cycl values than the corresponding O‐bridged rhodamines, as the LUMO is stabilized by the silicon atom [97] . This means spontaneous blinking is possible, even when the intramolecular nucleophile remains a carboxy group [98] . Silicon‐rhodamine (SiR‐carboxyl, Figure 11b) was used in super‐resolution imaging (STORM/GSDIM) [99] .…”
Section: Photochemical Mechanisms Of Fluorophores Used In Smlmmentioning
confidence: 99%
“…Silanyl-substituted fluorescein SiliF was also synthesized, which allowed the authors to perform dual-color SMLM imaging. [98] Urano and co-workers used a quantum-chemical calculation and rational design approach to design and synthesize a carbon-bridged rhodamine derivative HMCR550 that spontaneously blinks. [100] This method allows the blinking properties of a candidate fluorophore to be predicted, without the need to synthesize a variety of potential structures and obtain experimental measurements.…”
Section: Spontaneous Switching In Rhodaminesmentioning
confidence: 99%